ANALISIS KEBUTUHAN MODUL AJAR BIOLOGI MATERI VIRUS BERBASIS PjBL BERBANTUKAN APLIKASI KODULAR URGENSI PENINGKATAN KETERAMPILAN BERPIKIR KRITIS - Kumala, Diana; Wardhani, Sri; Astriani, Meli (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
This study aims to analyze teachers’ needs in developing project-based learning (PjBL) modules to address students’ learning requirements on the topic of viruses. The research was conducted at SMA Negeri 1 Indralaya Selatan, SMA Negeri 1 Indralaya, SMA Negeri 1 Indralaya Utara, and SMA Negeri 1 Tanjung Raja. Data were collected through documentation and interviews, and analyzed using a descriptive qualitative approach. The findings reveal that the application of PjBL in teaching virus-related material remains suboptimal. Teachers face several challenges, including: (1) difficulties in understanding and designing teaching modules; (2) uncertainty in selecting appropriate learning models; and (3) continued reliance on manually created, non-digital modules. From the students’ perspective, challenges include: (1) being required to study independently with minimal support; (2) limited engagement in practical or hands-on activities; and (3) low motivation due to the predominance of lecture-based instruction. In light of these findings, the study suggests the development of electronic project-based teaching modules using the Kodular application as a solution to enhance students’ critical thinking skills and provide more meaningful and engaging learning experiences.